The Role of the Environment and Type of Exercise on Acute Adrenal Modulation and Perceived Distress of Breast Cancer Survivors Practising Light-Intensity Physical Exercise - Andrea Di Blasio; Teresa Morano; Federica Lancia; Gianluca Viscioni; Ines Bucci; Simona Grossi; Alessandra Cimini; Ettore Cianchetti; Sara Verrocchio; Pascal Izzcupo; Antonino Grassadonia; Giorgio Napolitano (Archives of Breast Cancer, 2022)
Background: Distress and adrenal balance of breast cancer survivors (BCS) are key elements of their psychophysical health, and increasing evidence has shown both physical exercise and the natural environment are effective for their modulation. The aim of the study was to evaluate the acute effects of the environment and type of light intensity workouts, on distress, salivary cortisol and dehydroepiandrosterone sulfate (DHEA-S) in BCS. Methods: Twenty-four BCS participated in six different workouts, each with the same duration and intensity. Three of them were conducted in natural environments – walking (Wnature), canoeing with assistance (Cnature) and a mix of myofascial and yoga exercises (MYnature). The others were conducted in an urban environment, namely walking (Wurban), or an indoor environment, namely mobilisation and light upper body exercises (MCgym) and a mix of myofascial and yoga exercises (MYgym). Before and after each workout, the Distress Thermometer was completed and saliva was collected. Results: Workouts practised in natural environments elicited a higher reduction in cortisol and the cortisol to DHEA-S ratio and a greater DHEA-S increase compared with workouts practised in urban and indoor environments. Overall, Cnature and MYnature were the best activities; among those practised in urban and indoor environments, MYgym elicited the best results. Distress was not acutely reduced after Wurban and MCgym. Conclusion: Natural environments seem to provide the best management of distress, cortisol, DHEA-S and their balance when working out at light intensities. The simultaneous presence of forests and rivers seems to be the key element of the observed results.